2021
DOI: 10.1021/acs.est.1c01819
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide-Induced Shifts in the Periphyton Community Composition Indirectly Affect Feeding Activity and Physiology of the Gastropod Grazer Physella acuta

Abstract: Herbicides are well known for unintended effects on freshwater periphyton communities. Large knowledge gaps, however, exist regarding indirect herbicide impacts on primary consumers through changes in the quality of periphyton as a food source (i.e., diet-related effects). To address this gap, the grazer Physella acuta (Gastropoda) was fed for 21 days with periphyton that grew for 15 days in the presence or absence of the herbicide diuron (8 μg/L) to quantify changes in the feeding rate, growth rate, and energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 72 publications
2
2
0
Order By: Relevance
“…The highest abundances were measured for C. polonicus and M. glauca , and the lowest one for Phormidium sp . These findings are in line with previous studies that identified these phototrophic species in either natural in situ periphyton or periphyton grown in microcosms 11 , 47 , 48 , demonstrating the ecological relevance of our synthetic microbial community.
Fig.
…”
Section: Resultssupporting
confidence: 92%
“…The highest abundances were measured for C. polonicus and M. glauca , and the lowest one for Phormidium sp . These findings are in line with previous studies that identified these phototrophic species in either natural in situ periphyton or periphyton grown in microcosms 11 , 47 , 48 , demonstrating the ecological relevance of our synthetic microbial community.
Fig.
…”
Section: Resultssupporting
confidence: 92%
“…The highest abundances were measured for C. polonicus and M. glauca, and the lowest one for Phormidium sp. These findings are in line with previous studies that identified these phototrophic species in either natural in-situ periphyton or periphyton grown in microcosms [11,47,48], demonstrating the ecological relevance of our synthetic microbial community.…”
Section: Microbial Diversity and Composition During Periphyton Establ...supporting
confidence: 92%
“…There is some evidence that herbicides may affect the FAs composition of microalgae by interfering with vegetal lipid metabolism (Demailly et al, 2019;Gonçalves et al, 2021). Herbicides may also induce changes in microorganism community structure of periphyton by selecting for more tolerant species that differ in FA composition (Konschak et al, 2021). For example, diatoms are known to be rich in EPA, while green algae are characterised by high content of ALA and bacteria by C18:1n9, C16:0 and C18:0.…”
Section: Introductionmentioning
confidence: 99%